An Improvement on the Soft Reliability-Based Iterative Majority-Logic Decoding Algorithm for LDPC Codes - Ngatched, T M N; Alfa, A S; Cai, J (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
This paper presents an improvement of the reliability-based iterative majority-logic decoding algorithms for regular low-density parity-check (LDPC) codes proposed by Huang et al. We improve the computation of the extrinsic information that is used to update the reliability measure of each received bit in each iteration with some kind of reliability measures of the check-sums that are orthogonal on the considered bit. The improved algorithm achieves a significant gain over the standard one with only a modest increase in computational complexity.